Odpowiedzi

  • Użytkownik Zadane
2010-02-23T13:56:17+01:00
13x-2y+7-9x+y-4-3=4x-y=4*0,2+1=0,8+1=1,8
n²+n-7+3n²-n-9-n+16=4n²-n=4*1/4+1/2=1+1/2=3/2
3 2 3
Najlepsza Odpowiedź!
2010-02-23T13:57:00+01:00
13x-2y+7-9x+y-4-3=4x-y=4*(0,2)-(-1)=0,8+1=1,8

n2+n-7+3n2-n-9-n+16=4n2-n=4*(-1/2)2-(-1/2)=1+1/2=1 1/2
5 4 5
2010-02-23T13:59:08+01:00
Dla x= 0,2, y= -1
13x - 2y + 7 - 9x + y - 4 - 3 = 4x - y
4x - y = 4 * 0,2 - (-1) = 0,8 + 1 = 1,8


Dla n= - ½ = -1/2
n² + n -7 + 3n² - n - 9 - n + 16 = 4n² - n
4n² - n = 4 * (-1/2)² - (-1/2) = 4 * 1/4 + 1/2 = 1 + 1/2 = 1,5
6 2 6